2004
DOI: 10.1074/jbc.m403096200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of the Differential Sensitivity of Nematode and Mammalian Muscle to the Anthelmintic Agent Levamisole

Abstract: Levamisole is an anthelmintic agent that exerts its therapeutic effect by acting as a full agonist of the nicotinic receptor (AChR) of nematode muscle. Its action at the mammalian muscle AChR has not been elucidated to date despite its wide use as an anthelmintic in humans and cattle. By single channel and macroscopic current recordings, we investigated the interaction of levamisole with the mammalian muscle AChR. Levamisole activates mammalian AChRs. However, single channel openings are briefer than those act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…We demonstrated that key residues of the principal face, Y190 located in loop C and G153 located in loop B, are also required for GABA activation of muscle nAChR. The effects of aY190F and aG153S mutations on muscle nAChR activation have been well characterized Salamone et al, 1999;Grutter et al, 2003;Rayes et al, 2004;Mukhtasimova et al, 2009;Auerbach, 2011, 2013;Jadey et al, 2013). In parallel with the changes observed for ACh, GABA responses are increased in aG153S mutant and are negligible in aY190F mutant.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…We demonstrated that key residues of the principal face, Y190 located in loop C and G153 located in loop B, are also required for GABA activation of muscle nAChR. The effects of aY190F and aG153S mutations on muscle nAChR activation have been well characterized Salamone et al, 1999;Grutter et al, 2003;Rayes et al, 2004;Mukhtasimova et al, 2009;Auerbach, 2011, 2013;Jadey et al, 2013). In parallel with the changes observed for ACh, GABA responses are increased in aG153S mutant and are negligible in aY190F mutant.…”
Section: Discussionmentioning
confidence: 52%
“…Single-channel kinetic analysis of aG153S nAChR revealed a markedly decreased rate of ACh dissociation, which causes the mutant nAChR to open repeatedly forming bursts Rayes et al, 2004) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…6). At this positive potential, openchannel block is almost undetected (Neher and Steinbach, 1978;Rayes et al, 2004). This observation together with the fact that a reduction in peak current by channel block is not observed in the control chimera at 500 M pyrantel (see above) indicate that the reduction in the maximum response is originated from a reduced efficacy and not from channel block.…”
Section: Pyrantel Activation Of Nicotinic Receptors 1313mentioning
confidence: 57%
“…By acting as potent agonists of nematode AChRs, without being rapidly degraded, these drugs produce body-wall muscle hypercontraction, paralysis, and ultimately death of C. elegans and parasitic nematodes. These anthelmintics are highly selective for nematode AChRs, whereas they are very low-efficacy agonists of vertebrate muscle AChRs (Rayes et al, 2004).…”
Section: Introductionmentioning
confidence: 99%